Analysis of Instability Mechanism and Induced Cause of Urban Pavement in Xining City, China - Gan Qi; Zhenyu Wang; Yu Chen; Chun Zhu; Dazhong Ren; Tao Tian; Fu Yang (Advances in Materials Science and Engineering)
As a large human gathering place, the city directly causes huge property losses and casualties due to the ground collapse accident every year. In order to explore the causes and damage characteristics of urban ground collapse, taking Xining City, Qinghai Province, as an example, this paper analyzes the accidental factors causing ground collapse through on-site geological exploration and then expounds the deformation characteristics of urban ground collapse by using the numerical simulation method of Fluent and PFC. Using the collapsible balance method, it is obtained that the insufficient thickness of the top plate of the Loess Soil Subgrade in the collapse pit area is the inevitable factor causing the final collapse. The results show the following: (1) The failure of water supply pipe is an accidental factor leading to the formation of underground cavity, and the ground collapse accident is hidden, sudden, and of high risk, and its deformation and failure development process is slow. (2) The critical thickness of the roof above the air raid shelter is about 22 m, and the actual thickness is about 11.6 m, which is prone to deformation and uneven settlement, which is also an inevitable factor causing ground collapse. (3) The numerical simulation study shows that the final formation deformation range is about 16 m. At this time, the height of the formed cavity is about 9 m. The plastic zone tends to develop around, and the maximum settlement position appears above the air raid shelter. (4) The collapse process includes four stages: water supply pipeline leakage, underground cavity formation, collapse critical state, and ground collapse. This research and analysis provides theoretical guidance and scientific basis for the investigation, measurement, detection, and monitoring of various underground pipe networks of urban roads.